Penilaian Kinerja Dengan Menggunakan Malcolm Baldrige Education Criteria for Performance Excellence (MBECfPE) 2013-2014 Pada Program Studi Teknik Industri President University - Reni Renita; Anastasia L. Maukar (JIE Scientific Journal on Research and Application of Industrial System, 2018)
President University, located in Cikarang, has 14 study programs. The institution concerns to do continuous improvement through the Self Evaluation. This research was done from September 2015 to January 2016 and the aim of this resesarch is to conduct the Industrial Engineering study program performance measurement using Malcolm Baldrige Education Criteria for Performance Excellence (MBECfPE) 2013-2014. Based on the result,  leadership, strategic planning, customer focus, knowledge measurement, analysis and management, worker focus, operasional focus, and result criteria get the percentage of  65.29%, 76.42%, 74.43%, 69.49%, 70.92%, 67.58%, and 67.28% respectively.  The lowest result of sub criteria occurs on senior leadership with 59.93%. Meanwihle, strategy implementation sub criteria achieve the highest percentage of 77.15%. Total criteria measurement is 689.61 of 1000, which means the position of this study program in Industry Leader level